Torque Scaling Of Bilateral Control Master-Slave System For External Loads - Mohammed Aldabas, Sari Abdo Ali (2019)
In robotic field, haptics technologies are implemented to participate in increasing safety to human operators in many application fields such as medical devices, industrial manufacturing, and hazardous environments. Bilateral teleoperation is a part of real-world haptics that initiate two way of information teleoperation between two systems; the master system and the slave system. A person operates the master system to control a slave system that contact with the environment. The objectives of the experiments are conducted to investigate the effects of the variation of the bilateral controller parameters on the stability and the transparency, and to design and validate haptic bilateral controller to control the position and the torque when an external load is applied to the controller. The interaction between the slave system with the environment is fed back to the master system and the operator can sense it through the master system. The bilateral controller controls the position and the torques of the actuation motors. The bilateral control system contains PD controller for position control, force controller, disturbance observer and reaction torque observer. The disturbance observer reduces the disturbance of the system and the reaction torque observer estimates the external reaction torques. The bilateral controller is designed to make the slave system track the master system position trajectories so that the motion of the master and the slave motors are in synchronization. Furthermore, the master system and the slave system are built to have single link manipulator each. The effects of the external loads on the stability of the bilateral controller system have not been studied yet. If a load is attached to the bilateral controller on the slave side, the stability of the controller deteriorated. Additionally, the external load requires more operational force exerted by the human operator on the slave side. The contribution of the project is to propose torque scaling method to improve the stability and to reduce the effects of the load on the master side. The proposed method enables the operator to move the master manipulator and the slave manipulator will track the motion without more operational force. The proposed method scales up the master torque in order to be able to move the slave manipulator with the load on it. The proposed scaling factor is the ratio of load mass and the slave manipulator mass to the master manipulator mass the validation of the designed bilateral controller is done through experiments of free motion and through contact motion. The experiments showed that the position tracking of the deferential mode of the controller is improved. The error of the master manipulator position and the slave manipulator position is zero. The torque error of the common mode is 0.05. Throughout the experimentation, it showed that the scaling method succeeded in scaling the torque of the controller without affecting the accuracy of the position tracking.